Urgensi Sikap Dermawan Menurut Hadis - Triani, Rena Ajeng (Jurnal Riset Agama, 2022)
The purpose of this study is to discuss the urgency of generosity in the hadith. This research method uses a qualitative type through literature study with content analysis. The results and discussion of this study include general views on generosity, hadith about generosity, and the application of generosity according to hadith. This study concludes that Islam is a perfect religion. Not only regulating habluminallah but also regulating habluminannas, which must be done properly, correctly and in balance. One of the teachings of Islam that Allah has commanded to his people is caring and giving. Confession of the truth of a person's faith can be measured by his giving behavior. Giving is not a bad deed, but on the contrary, it is a commendable act. The generous person is close to Allah, close to heaven, close to humans, and far from hell.